A call to action on women's health: putting corporate CSR standards for workplace health on the global health agenda. Issue 1 (December 2016) - Wofford, David; MacDonald, Shawn; Rodehau, Carolyn
Abstract Business operates within a Corporate Social Responsibility (CSR) system that the global health community should harness to advance women's health and related sustainable development goals for workers and communities in low- and middle-income countries. Corporations and their vast networks of supplier companies, particularly in manufacturing and agribusiness, employ millions of workers, increasingly comprised of young women, who lack access to health information, products and services. However, occupational safety and health practices focus primarily on safety issues and fail to address the health needs, including reproductive health, of women workers. CSR policy has focused on shaping corporate policies and practices related to the environment, labor, and human rights, but has also ignored the health needs of women workers. The authors present a new way for global health to understand CSR – as a set of regulatory processes governed by civil society, international institutions, business, and government that set, monitor, and enforce emerging standards related to the role of business in society. They call this the CSR system. They argue that the global health community needs to think differently about the role of corporations in public health, which has been as "partners, " and that the global health practitioners should play the same advocacy role in the CSR system for corporate health policies as it does for government and international health policies.